Analysis of Bgenome derived simple sequence repeat (SSR) markers in Musa spp. - Oriero, C.E.; Odunola, O.A.; Lokko, Y.; Ingelbrecht, I.L. (2006)
A study was conducted to investigate the genetic variability between 40 Musa genotypes maintained at the Musa germplasm collection of the International Institute for Tropical Agriculture, Ibadan using nine B-genome derived simple sequence repeat (SSR) markers. The nine primers produced reproducible and discrete fragments and generated a total of 23 alleles with an average of 2.1. The hierarchical cluster analysis showed clusters of diploid cultivars separate from triploid ones (with the exception of TMB149 (BB) and TMB131 (AB)). Average gene diversity was He = 0.412, and differentiation, given by the fixation index (FST) was low at 0.131.